Mortality Salience and Cultural Cringe: The Australian Way of Responding to Thoughts of Death. (November 2014) - Kashima, Emiko S.; Beatson, Ruth; Kaufmann, Leah; Branchflower, Sarah; Marques, Mathew D.
Terror Management Theory predicts that mortality salience (MS) instigates cultural worldview defenses, especially among individuals with lower self-esteem. That MS intensifies positive evaluations of pro-U.S. essay authors, and negative evaluations of anti-U.S. essay authors have been documented as supportive evidence. However, the evidence to date may have been limited to where praising for the former and rejection of the latter authors is consistent with a shared cultural script and thus normative. In the case of Australian people, the cultural script of cringe prescribes them to evaluate their country modestly and to reject high praise of their country. We therefore predicted that MS (vs. control) should lead Australians, with low self-esteem in particular, to evaluate pro-Australia essay authors less positively while not affecting their evaluations of anti-Australia essay authors. Results from two studies were consistent with this prediction. It is important to distinguish MS effects on adherence to cultural norms from those on reaffirming collective self-esteem, and to consider relevant cultural scripts when interpreting evidence for worldview defenses.